(untitled) (Journal of the Management Sciences, 2024)
This study ascertained the effect of green accounting disclosure on financial performance of listed consumer goods firms in Nigeria, using environmental protection disclosure and corporate donation. Ex post facto research design was adopted for the study. A sample of 18 consumer goods firms was used and data extracted from the companies audited annual reports and accounts. Using regression analysis, it was established that environmental protection disclosure and corporate donation with firm size as the control variable were significant. This shows the extent to which consumer goods firms disclose information voluntarily, particularly regarding environmental protection, corporate donations, and employee welfare, can significantly influence stakeholders’ perceptions and decisions. Based on the findings of the study, it was recommended that there should be constant green accounting disclosure by the firms for mitigating its environmental impact and promoting sustainable practices. This will enable them share with their stakeholders to demonstrate their commitment toward environmental responsibility.